If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2x + 2 = -64 Reorder the terms: 4 + 2 + -2x = -64 Combine like terms: 4 + 2 = 6 6 + -2x = -64 Solving 6 + -2x = -64 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -2x = -64 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = -64 + -6 -2x = -64 + -6 Combine like terms: -64 + -6 = -70 -2x = -70 Divide each side by '-2'. x = 35 Simplifying x = 35
| n=40-10 | | 2n^2-6=0 | | 4-2x=10+x | | 10-3b=-7b+6b | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 4y-a=5a+6(3-y) | | Ln40/ln4 | | 2-(1/3)t | | 6+z(9)=9 | | -4(-3x-8)-4x+8= | | 15/30=6/x | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -100=n+8 | | 15/30=6/x | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -8x+3+3x=13 | | 7x=3(3x-4) | | 7x+5(4-2x)=5 | | (x-35)+90+43=180 | | (8x+4)(8x-4)=y | | -6x+7(2x+6)=142 | | -90-6x=48-12x |